Usefulness of Soluble Transferrin Receptor in the Diagnosis of Iron Deficiency Anemia in Rheumatoid Arthritis Patients in Clinical Practice. (12th October 2022) - Günther, Florian; Straub, Rainer H.; Hartung, Wolfgang; Fleck, Martin; Ehrenstein, Boris; Schminke, Louisa
Abstract : Aim . We analyzed the added value of sTfR measurement in routine clinical practice to standard parameters (SP) of iron deficiency in the detection of iron deficiency anemia (IDA) in patients with rheumatoid arthritis (RA). Methods . Blood samples from 116 patients with RA were analyzed in a prospective study. Based on biochemical parameters, patients were classified as having IDA, anemia of chronic disease (ACD), IDA with concomitant ACD (ACD/IDA), or "other anemia." Sensitivity, specificity, positive (PPV), and negative predictive values (NPV) of sTfR and SP of iron status alone and in combination were calculated for the diagnosis of IDA in general, i.e., IDA or ACD/IDA. Results . In the whole sample, with regard to the diagnosis of iron deficiency (IDA or ACD/IDA), sTfR had a higher sensitivity compared both to the combined use of SP and to the combination of SP with sTfR (80.9% versus 66.7/54.8%). Specificity, PPV and NPV did not differ substantially. When patients were stratified in groups with high (CRP levels above the median, i.e., 24.1 mg/l) and low (CRP levels less or equal to the median) inflammation, the diagnostic superiority of sTfR was restricted to patients with high inflammation. In this group, the diagnostic performance of sTfR was superior both to the combined use of SP and the combination of SP with sTfR with higher sensitivity (100% versus 52.4%) and NPV (100% versus 77.7/76.7%) and comparable specificity and PPV. Conclusion . For the detection of iron depletion (IDA or ACD/IDA) in anemic RA patients, sTfR is superior to SP of iron deficiency only in highly inflammatory states.